Investigation of the impact of the layer formation of AlSi coated boron-manganese steel in regard to friction and wear - He, Franz; Merklein, Marion (International Conference on Hot Sheet Metal Forming of High Performance Steel, 2022)
With the increase in electric vehicles, factors for limiting reach due to finite battery capacity have found increased significance. Lightweight solutions are needed, amongst which the construction with ultra-high strength steels have been established as the industrial standard. These materials are able to bridge the gap between providing reduced part weight while improving mechanical properties. While cold forming faces various challenges such as high forming resistance and spring-back behavior, hot stamping of boron manganese steels allow for reduced forming forces and increased dimensional accuracy. The sheet is austenized at temperatures above 850 °C which leads to a phase change in the material and decrease in tensile strength. Since uncoated material suffers from decarburization and scale formation, which negatively inform the forming process and final part quality, aluminum silicon coatings (Al-Si) are applied. Additionally, lubricants lose their properties at higher process temperatures, leading to increased friction and severe wear in the process. Previous investigations have shown that furnace holding times influence the layer formation of AlSi-based coatings due to diffusion processes. Within this study, the influence of furnace holding times and subsequent layer formation on the friction and wear behavior as well as interdependencies with other relevant process parameters is investigated. To this end single sided strip drawing tests are performed with an industrial standard coating AS150 and analyzed in regard to the friction coefficient. Additionally, the tool sided wear is investigated through contactless 3D measurement. The results of this study help to improve the process understanding of the tribological conditions within the hot stamping process and to develop tailored measures for reducing tool wear.
Keywords: Friction; wear; hot stamping; 22MnB5